2017
DOI: 10.3390/ijms18071567
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Molecular Mechanisms of Interface Buildup and Stability in Porous Si/Eumelanin Hybrids

Abstract: Porous Si/eumelanin hybrids are a novel class of organic–inorganic hybrid materials that hold considerable promise for photovoltaic applications. Current progress toward device setup is, however, hindered by photocurrent stability issues, which require a detailed understanding of the mechanisms underlying the buildup and consolidation of the eumelanin–silicon interface. Herein we report an integrated experimental and computational study aimed at probing interface stability via surface modification and eumelani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…Indeed the ability of eumelanin functionalization to extend the absorption range of PSi towards longer wavelengths has been demonstrated. 1,2 The basic building blocks of eumelanin are 5,6-dihydroxyindole (DHI) -like molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the ability of eumelanin functionalization to extend the absorption range of PSi towards longer wavelengths has been demonstrated. 1,2 The basic building blocks of eumelanin are 5,6-dihydroxyindole (DHI) -like molecules.…”
Section: Introductionmentioning
confidence: 99%
“…29 In our previous proof-of-concept investigations we reported PSi/eumelanin nanocomposites for photovoltaic applications and demonstrated the ability of eumelanin functionalization to enhance substrate photoconductivity. 25,31 However, despite the improved photoconductivity produced by eumelanin functionalization, the reduced photocurrent stability over days limits the ability to accomplish steps forward toward technology transfer. 31 Apparently, the stability issues stem from the characteristics of the PSi/eumelanin hybrid, including chiefly the buildup of the polymer within the pores in relation to the nature and shape of the inorganic material (irregular dendritic pores are present in the case of PSi).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Future advancements in the development of melanin-based functional materials are expected to greatly benefit from the rational design of hybrid organic-inorganic systems and from a thorough understanding of the fundamental interaction mechanisms at the interface. In this Special Issue, Pinna et al, reported a combined experimental and computational investigation aimed at modeling the melanin-porous silicon interface and at elucidating the factors controlling its stability [ 9 ]. The results showed that oxidation of the inorganic surface and the oligomer components improves adhesion and enhances photocurrent stability.…”
Section: Hybrid Design For Boosting Performancementioning
confidence: 99%